Population genomic analyses of protected incense trees Aquilaria sinensis reveal the existence of genetically distinct subpopulations - Law, Sean Tsz Sum; Nong, Wenyan; Yip, Ho Yin; Liu, Eric Ka Yip; Ng, Terence Pun Tung; Tsang, Ryan Ho Leung; Xia, Nianhe; Shaw, Pang-Chui; Lam, Hon Ming; Lau, David Tai Wai; Hui, Jerome Ho Lam (Frontiers in Ecology and Evolution, 2023)
The incense tree Aquilaria sinensis (Thymelaeaceae) can produce agarwood with commercial values, and are now under threats from illegal exploitation in Hong Kong, impairing the local population and biodiversity. Together with other species of Aquilaria, they are listed in the CITES Appendix II, which strictly regulates their international trade. To understand the population structure of A. sinensis and to make relevant conservation measures, we have sequenced 346 individuals collected in Hong Kong and southern mainland China. Population genomic analyses including principal component analysis, neighbour-joining tree construction, ADMIXTURE and hierarchical pairwise-FST analyses suggested genetically distinct populations are contained in certain areas. Genomic scan analyses further detected singlenucleotide polymorphism (SNP) outliers related to plant defence, including the CYP71BE gene cluster. In addition to the population analyses, we have developed a modified hexadecyltrimethyl-ammonium bromide (CTAB) DNA extraction protocol for obtaining DNA from agarwood samples in this study, and resequencing of DNA extracted from two agarwood samples using this method allows us to successfully map to the sample corresponding localities in the phylogenetic tree. To sum up, this study suggested that there is genetically distinct subpopulation of incense tree in Hong Kong which would require special conservation measures, and established a foundation for future conservation measures.